2019
DOI: 10.1530/edm-19-0013
|View full text |Cite
|
Sign up to set email alerts
|

Exceptional diazoxide sensitivity in hyperinsulinaemic hypoglycaemia due to a novel HNF4A mutation

Abstract: Summary Diazoxide is the first-line treatment for patients with hyperinsulinaemic hypoglycaemia (HH). Approximately 50% of patients with HH are diazoxide resistant. However, marked diazoxide sensitivity resulting in severe hyperglycaemia is extremely uncommon and not reported previously in the context of HH due to HNF4A mutation. We report a novel observation of exceptional diazoxide sensitivity in a patient with HH due to HNF4A mutation. A female infant presented with severe persistent neonatal hypoglycaemia … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…The HNF4A gene encodes for the transcription factor hepatocyte nuclear 4a which controls the expression of genes involved in insulin secretion 3 . The sibling of one of these patients has been reported previously and was known to have HH that was very sensitive to diazoxide treatment, requiring lower doses 4 and developed hyperglycaemia on traditional doses of diazoxide. It may be that this particular mutation in HNF4A (p.Ser419Ter; c.1256C>G) leads to exceptional sensitivity to diazoxide or that mutations in HNF4A in general require smaller doses of diazoxide.…”
Section: Sga (N = 15) Non‐sga (N = 19) Preterm Term Preterm Termmentioning
confidence: 99%
“…The HNF4A gene encodes for the transcription factor hepatocyte nuclear 4a which controls the expression of genes involved in insulin secretion 3 . The sibling of one of these patients has been reported previously and was known to have HH that was very sensitive to diazoxide treatment, requiring lower doses 4 and developed hyperglycaemia on traditional doses of diazoxide. It may be that this particular mutation in HNF4A (p.Ser419Ter; c.1256C>G) leads to exceptional sensitivity to diazoxide or that mutations in HNF4A in general require smaller doses of diazoxide.…”
Section: Sga (N = 15) Non‐sga (N = 19) Preterm Term Preterm Termmentioning
confidence: 99%
“…The first-line treatment for CHI is diazoxide, which binds to the linker region of the SUR1 subunit of the K ATP channels and suppresses β-cell insulin secretion by forcing the channels to remain open [ 6 , 24 , 25 , 26 , 27 , 28 ]. Recent studies suggest diazoxide as the drug of choice and recommend a starting dose of 5 mg/kg/day with target values of no more than 20 mg/kg/day [ 6 , 25 , 27 , 28 ]. One study reported that high diazoxide doses of >5 mg/kg/day, necessary to maintain euglycaemia, can be considered a severity and prognostic marker in the early stages of diagnosis [ 29 ].…”
Section: Treatmentmentioning
confidence: 99%
“…In view of the possible side effects, the optimal dose of diazoxide should be as low as possible to maintain euglycaemia [ 27 ]. Diazoxide hypersensitivity, which manifests as hyperglycaemia at minimal doses of diazoxide, is very rare and is usually associated with a mutation in the HNF4A gene [ 25 ]. Hypertrichosis is the most common adverse effect of diazoxide and its degree is not correlated with the dose of the drug [ 28 , 32 ].…”
Section: Treatmentmentioning
confidence: 99%
“…Their group suggests lower doses of diazoxide (1.5 mg/kg/d), instead of traditional dosing (5 mg/kg/d), in patients with this mutation to prevent this rare complication. 5 It is now worth considering screening for HNF4A mutations before initiating diazoxide treatment. Kudos to Balsam et al, who identified a rare but serious complication of diazoxide treatment that may now be preventable.…”
mentioning
confidence: 99%